2007
DOI: 10.1097/mpa.0b013e31805b8319
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Versus Alcohol-Related Infected Pancreatic Necrosis Similarities and Differences in the Follow-Up

Abstract: Patients after alcohol-induced IPN had lower quality of life compared with biliary etiology. Biliary and alcohol-induced IPN patients after surgical treatment have nonsignificant differences of endocrine and exocrine pancreatic functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 25 publications
0
17
0
1
Order By: Relevance
“…There were two RCTs [ 30 , 55 ] for PERT versus placebo and one for the endoscopic versus surgical step-up approach [ 64 ]. Ten studies [ 36 , 44 , 46 , 47 , 49 , 51 , 53 , 54 , 57 , 64 ] had a consecutive cohort design, and the remainders were non-consecutive cohort studies. Three studies [ 55 , 56 , 64 ] were multicenter.…”
Section: Resultsmentioning
confidence: 99%
“…There were two RCTs [ 30 , 55 ] for PERT versus placebo and one for the endoscopic versus surgical step-up approach [ 64 ]. Ten studies [ 36 , 44 , 46 , 47 , 49 , 51 , 53 , 54 , 57 , 64 ] had a consecutive cohort design, and the remainders were non-consecutive cohort studies. Three studies [ 55 , 56 , 64 ] were multicenter.…”
Section: Resultsmentioning
confidence: 99%
“…1 This is supported by clinical data that suggest that alcoholics are predisposed to acute pancreatitis, as well as to an earlier onset, more frequent episodes, and an increased risk of chronic pancreatitis. 2,3 Experimental models of alcoholic pancreatitis in rats have revealed that endotoxemia can initiate acute and chronic alcoholic pancreatitis and that the inflammatory response to injury is more pronounced in alcoholic pancreatitis than in nonalcoholic pancreatitis. 4,5 Increased gut permeability and subsequent bacterial translocation across the mucosal barrier have been described in alcoholics.…”
Section: Introductionmentioning
confidence: 99%
“… 22 , 24 Alcoholics seem more susceptible to AP, a condition associated with an earlier onset, more frequent episodes and an increased risk of CP. 25 , 26 , 27 , 28 Alcoholic patients also have elevated serum LPS concentrations, which have been correlated with the severity of alcoholic AP. 29 , 30 Interestingly, chronic sub-clinical endotoxemia has been linked to insulin resistance, obesity, and diabetes, as well as cardiovascular disease, indicating that LPS has important clinical relevance not only for alcoholics with pancreatitis, but also for other metabolic disorders.…”
mentioning
confidence: 99%